2014
DOI: 10.4103/2230-8229.134772
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of pediatric cardio- pulmonary resuscitation in the community of Al-Khobar city

Abstract: Background:The history of resuscitation going back thousands of years has been reported in literature throughout history. This concept has undergone several decisive revolutionary changes particularly in pediatrics. Although the cardio-pulmonary resuscitation (CPR) is relatively new in pediatrics, progress has been remarkable in the last a few decades. As it becomes more popular, especially under the influence of globalizing media, CPR also becomes a life requirement that is not restricted to health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…However, it was responsible for 9.1% not performing CPR in the US study [ 35 ], in which both genders were willing to attend a CPR training course whenever possible. Previous studies in Saudi Arabia reported that 59% of females were not performing CPR compared to 29% of males [ 30 ]. In general, male's students have more knowledge about CPR as compared with female students; the reason is male students are more interested to do outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was responsible for 9.1% not performing CPR in the US study [ 35 ], in which both genders were willing to attend a CPR training course whenever possible. Previous studies in Saudi Arabia reported that 59% of females were not performing CPR compared to 29% of males [ 30 ]. In general, male's students have more knowledge about CPR as compared with female students; the reason is male students are more interested to do outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study targeting the general dentists in Kuwait, 64% showed low knowledge, while only 36% have high knowledge about CPR [ 29 ]. In Saudi Arabia, few studies about CPR knowledge were conducted in a study on 753 subjects in Al-Khobar city in which 80.8% of the females and 86.5% of the males were totally unaware of CPR; however, 88.7% of all participants were willing to attend CPR courses in the future [ 30 ]. In another study conducted among secondary schools in Riyadh, 56% of the students did not have enough knowledge about CPR, and about 67% of all students wanted to know more about CPR [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also highlighted the urgent need for increased awareness of CPR among parents . To the best of our knowledge, only one study has evaluated the awareness of CPR among parents . That study found that the prevalence of CPR knowledge among parents was approximately 20%, but the factors associated with awareness of CPR were not evaluated.…”
mentioning
confidence: 99%
“…In fact, the average scores did not differ between those who had training and those who did not. The majority of teachers wanted more training (64.9%) and were willing to take a free course (78.4%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strong evidence that basic life support including cardiopulmonary resuscitation (CPR) improves survival rates after cardiac events, the awareness and training among citizens of Saudi Arabia is low [7]. Public awareness and knowledge on CPR was inadequate even among the younger population, and among parents with disabled children.…”
Section: Introductionmentioning
confidence: 99%